2017
DOI: 10.1186/s12998-016-0132-9
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal diagnostic ultrasound imaging for thickness measurement of four principal muscles of the cervical spine -a reliability and agreement study

Abstract: BackgroundThe reliability of musculoskeletal diagnostic ultrasound imaging (MSK-DUSI) for the evaluation of neck musculature has been sparsely documented in the research literature. Until now, research has featured a limited number of subjects and only few studies have tested for both inter- and intra-reliability using appropriate methodology.MethodsFour examiners conducted an inter- and intra-rater reliability and agreement study. Fifty females with and without neck pain (NP) between the ages of 20–70 were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 69 publications
1
15
0
1
Order By: Relevance
“…The different methodologies used in the ultrasound evaluation of the cervical muscles make comparisons between the studies limited. Many of them do not present the agreement analysis values, only evaluating the intraclass correlation coefficient [18]. One study [5], evaluating patients with chronic neck pain, corroborates our findings related to the ICC analysis of the cross-sectional area of the longus colli muscle at rest (ICC in our study: 0.68 to 0, 93).…”
Section: Discussionsupporting
confidence: 88%
“…The different methodologies used in the ultrasound evaluation of the cervical muscles make comparisons between the studies limited. Many of them do not present the agreement analysis values, only evaluating the intraclass correlation coefficient [18]. One study [5], evaluating patients with chronic neck pain, corroborates our findings related to the ICC analysis of the cross-sectional area of the longus colli muscle at rest (ICC in our study: 0.68 to 0, 93).…”
Section: Discussionsupporting
confidence: 88%
“…The third muscle layer is SC. The bright line is the fascial layer and the area enclosed by the line is the CSA of SC, as previous study described [14].…”
Section: Cross-sectional Area Of the Deep Neck Exors And Extensors Asmentioning
confidence: 71%
“…In recent years, various methods have been used to evaluate spinal muscles, including surface and needle electromyography, Magnetic Resonance Imaging (MRI), and Ultrasound (US) 6 , 7 , 10 , 11 , 12 , 13 ) . The MRI evaluations of patients with chronic tension-type headache and whiplash injury revealed that, thickness of sub-occipital muscle decreased compared to healthy controls 7 , 10 , 11 ) .…”
Section: Introductionmentioning
confidence: 99%